Chlamydia sequelae cost estimates used in current economic evaluations: does one-size-fit-all?. (9th June 2016) - Ong, Koh Jun; Soldan, Kate; Jit, Mark; Dunbar, J Kevin; Woodhall, Sarah C
Abstract : Background: Current evidence suggests that chlamydia screening programmes can be cost-effective, conditional on assumptions within mathematical models. We explored differences in cost estimates used in published economic evaluations of chlamydia screening from seven countries (four papers each from UK and the Netherlands, two each from Sweden and Australia, and one each from Ireland, Canada and Denmark). Methods: From these studies, we extracted management cost estimates for seven major chlamydia sequelae. In order to compare the influence of different sequelae considered in each paper and their corresponding management costs on the total cost per case of untreated chlamydia, we applied reported unit sequelae management costs considered in each paper to a set of untreated infection to sequela progression probabilities. All costs were adjusted to 2013/2014 Great British Pound (GBP) values. Results: Sequelae management costs ranged from £171 to £3635 (pelvic inflammatory disease); £953 to £3615 (ectopic pregnancy); £546 to £6752 (tubal factor infertility); £159 to £3341 (chronic pelvic pain); £22 to £1008 (epididymitis); £11 to £1459 (neonatal conjunctivitis) and £433 to £3992 (neonatal pneumonia). Total cost of sequelae per case of untreated chlamydia ranged from £37 to £412. Conclusions: There was substantial variation in cost per case of chlamydia sequelae used in published chlamydia screening economic evaluations, which likely arose from different assumptions about disease management pathways and the country perspectives taken. In light of this, when interpreting these studies, the reader should be satisfied that the cost estimates used sufficiently reflect the perspective taken and current disease management for their respective context.